The doll people [compact disc, unabridged] - Martin, Ann M., 1955- (Martin, Ann M., 1955- Doll people story.., 2011)
A family of porcelain dolls that has lived in the same house for one hundred years is taken aback when a new family of plastic dolls arrives and doesn't follow The Doll Code of Honor.